Factors associated with the development of neonatal hypoglycemia after antenatal corticosteroid administration: It's all about timing. Issue 2 (30th October 2021) - Zigron, Roy; Rotem, Reut; Erlichman, Ira; Rottenstreich, Misgav; Rosenbloom, Joshua I.; Porat, Shay; Rottenstreich, Amihai
Abstract: Objective: To determine the factors associated with neonatal hypoglycemia among neonates exposed to antenatal corticosteroid (ACS). Methods: A retrospective study conducted during 2017–2019 at a tertiary‐care center including all neonates delivered between 24 and 34 weeks of gestation after ACS administration. The primary outcome was neonatal hypoglycemia (<40 mg/dl). Results: Overall, 362 early preterm neonates, including 205 singletons and 157 twins, were exposed to ACS before delivery and constituted the study group. Of them, 275 (76.0%) were exposed to a single ACS course and 87 (24.0%) to an additional rescue ACS course. Neonatal hypoglycemia occurred in 84 (23.2%) neonates. The incidence of neonatal hypoglycemia was significantly higher in those delivered between 24 and 48 h after ACS administration compared with those delivered outside this time interval (10/25, 40.0% vs 74/337, 21.9%; P  = 0.049). In multivariate analysis, after adjusting for neonatal birth weight and gestational age, delivery within 24–48 h after ACS administration was the only independent risk factor associated with neonatal hypoglycemia (adjusted odds ratio 2.41, 95% confidence interval 1.03–5.68; P  = 0.044). Conclusion: Neonatal hypoglycemia occurred in over one‐fifth of those exposed to ACS, and was independently associated with delivery between 24 and 48 h after ACS administration. Abstract : Neonatal hypoglycemia occurs in over one‐fifth of neonates exposed to antenatal corticosteroid (ACS), and is independently associated with delivery within 24–48 h after ACS administration.